Examining The Effectiveness Of Writer’s Workshop And Interactive Writing On Preschool Emergent Writing And Attitude In The Northwest Zone Of Nigeria - Taofik, Hassan Mohammad (2024)
Preschool children hold immense writing potential that is rarely realized in traditional classrooms. This mixed-method, the quasi-experimental study focused on how best to teach these emergent writers. Comparing the effects of Interactive Writing and Writer’s Workshop instruction, the study provided a clearer picture of how these instructional approaches influence children’s emergent writing achievement and attitudes.